Contemporary Responses to The Criticism of Islamic Banks in Malaysia - Chowdhury, Mohammad Abdul Matin; Masud, Md. Abdullah Al; Atiullah, Md; Tanvir, Jayadul Islam (European Journal of Islamic Finance, 2020)
The rapid growth of Islamic banks has become a focus of all investors and consumers. Malaysia has put in a lot of effort to develop and gather acceptance from all citizens of the country for Islamic banking. Hence, throughout the sector’s expansion, there have been several critics, such asshariah scholars, investors, and consumers. For instance; a lack of shariah experts in both economics and shariah itself, interest rates as benchmark, similarities with conventional banks etc. As the Malaysian Islamic banking system is growing and expanding, as are its critics. Therefore, the main purpose of this study to provide adequate arguments on the contemporary criticisms and challenges being faced by Islamic banks in Malaysia. This study has adopted a qualitative approach; conducting semi-structured interviews and observations. The findings recognised shariah compliancy, interest rates as a benchmark, and a lack of shariah scholars are the most pertinent current issues for Islamic banks in Malaysia. Through the supports of scholars, policy makers, and consumers, these issues can be resolved over time with Islamic finance literacy. The outcome of this study may benefit policy makers, investors, Muslim consumers, as well as stakeholders of Islamic banking and finance.